Thymome = Thymomas - Marx, Alexander; Weis, Cleo-Aron Thias; Ströbel, Philipp (Der Pathologe, 2016)
Thymomas are rare tumors but are one of the most common mediastinal neoplasms in adults and exhibit an enormous variability in histological, biological and genetic features. The morphological spectrum within a given entity is enormous and some tumors with histological patterns of more than one entity are more common than pure histological subtypes. Due to a lack of subtype-specific markers classification of thymomas often requires complex diagnostic algorithms. The refined presentation including the definition of obligatory and optional features and of diagnostic immunohistochemical profiles, is the focus of the new World Health Organization (WHO) classification of thymomas, aiming at improving diagnostic reproducibility. This review highlights novel aspects of the WHO classification of thymomas and addresses typical differential diagnostic challenges with a focus on diagnostic pitfalls.